2021
DOI: 10.3389/fendo.2021.774257
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antibiotic Alterations in Gut Microbiota With Decreased Osseointegration of an Intramedullary Nail in Mice With and Without Osteomyelitis

Abstract: Treatment of osteomyelitis requires prolonged antibiotic therapy which significantly alters the gut microbiota. While the influences on bone mass and microstructure have been extensively studied, it is poorly understood what impact the changes in gut microbiota may have on the host response to osseointegration around an intramedullary nail implanted. Here, we explored the influence of gut microbiota on the bone osseointegration process around an implant under two conditions: implantation of an intramedullary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Although the abundance of most of these pathogenic microorganisms mentioned above was up-regulated in the gut microbiota, we are not sure whether the corresponding up-regulation of bacterial abundance in the intestinal tract was caused by the bacterial translocation from the bone tissue focus in FRI patients. However, in our previous study of animal osteomyelitis, the results showed that OTU numbers of Staphylococcus and Lysobacter were higher and that of Akkermansia was significantly lower in the mice with osteomyelitis than in the mice without osteomyelitis but only with an intramedullary nail ( Zhao et al, 2021 ). In addition, a gain in Streptococcus in fecal samples has also been found in new-onset Crohn’s Disease (CD) and has been associated with a higher recurrence of CD after surgery ( Gevers et al, 2014 ; Pascal et al, 2017 ; Zhou et al, 2018 b).…”
Section: Discussionmentioning
confidence: 85%
“…Although the abundance of most of these pathogenic microorganisms mentioned above was up-regulated in the gut microbiota, we are not sure whether the corresponding up-regulation of bacterial abundance in the intestinal tract was caused by the bacterial translocation from the bone tissue focus in FRI patients. However, in our previous study of animal osteomyelitis, the results showed that OTU numbers of Staphylococcus and Lysobacter were higher and that of Akkermansia was significantly lower in the mice with osteomyelitis than in the mice without osteomyelitis but only with an intramedullary nail ( Zhao et al, 2021 ). In addition, a gain in Streptococcus in fecal samples has also been found in new-onset Crohn’s Disease (CD) and has been associated with a higher recurrence of CD after surgery ( Gevers et al, 2014 ; Pascal et al, 2017 ; Zhou et al, 2018 b).…”
Section: Discussionmentioning
confidence: 85%
“…However, a new perspective was introduced by Zhao et al. in their 2021 study ( Zhao et al., 2021 ). Their research revealed that prolonged antibiotic treatment for OM disrupts the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…This regulation enhances bacterial resilience against the host’s oxidative responses, thus promoting increased tolerance ( Zafar and Saier, 2021 ). Research conducted by Zhao et al., 2021 has established that the prolonged use of antibiotics in OM treatment results in a reduction of the Bacteroidetes population, leading to decreased levels of inflammation ( Zhao et al., 2021 ). This evidence indirectly corroborates our hypothesis that Bacteroidia or Bacteroidales play a role in the development and progression of OM, mirroring the conclusions we reached through our MR analysis.…”
Section: Discussionmentioning
confidence: 99%